The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1083/jcb.135.4.1163
|View full text |Cite
|
Sign up to set email alerts
|

Distinct regions control transcriptional activation of the alpha1(VI) collagen promoter in different tissues of transgenic mice.

Abstract: Abstract. To identify regions involved in tissue specific regulation of transcription of the a l (VI) collagen chain, transgenic mice were generated carrying various portions of the gene's 5'-flanking sequence fused to the E. coli 13-galactosidase gene. Analysis of the transgene expression pattern by X-gal staining of embryos revealed that: (a) The proximal 0.6 kb of promoter sequence activated transcription in mesenchymal cells at sites of insertion of superficial muscular aponeurosis into the skin; tendons w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0
6

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 30 publications
(44 reference statements)
4
37
0
6
Order By: Relevance
“…In the peripheral nervous system, ColVI is abundantly expressed by Schwann cells and is present in the connective tissue of the endo-, peri-and epineurium (Braghetta et al, 1996;Chen et al, 2014a). It has been shown previously that ColVI has a role in regulating Schwann cell differentiation because it is expressed by immature Schwann cells in a neuregulin-dependent manner when they start differentiating into myelinating cells (Vitale et al, 2001).…”
Section: Nervous Systemmentioning
confidence: 99%
“…In the peripheral nervous system, ColVI is abundantly expressed by Schwann cells and is present in the connective tissue of the endo-, peri-and epineurium (Braghetta et al, 1996;Chen et al, 2014a). It has been shown previously that ColVI has a role in regulating Schwann cell differentiation because it is expressed by immature Schwann cells in a neuregulin-dependent manner when they start differentiating into myelinating cells (Vitale et al, 2001).…”
Section: Nervous Systemmentioning
confidence: 99%
“…Studies in transfected cells and in transgenic mice demonstrated that transcriptional regulation is the major determinant for the highly regulated and dynamic pattern expression of ColVI during development and in adult tissues. The data thus far available for the Col6a1 gene indicate a complex pattern of tissue-specific transcription that is dependent on different enhancer and silencer elements spread over a large genomic region and controlling expression in skin, tendons, joints, peripheral nerves, and skeletal muscles, respectively (Braghetta et al 1996). Muscle interstitial fibroblasts are the main source of ColVI in the ECM of skeletal muscle .…”
mentioning
confidence: 99%
“…As most of the extracellular matrix components, collagen VI is endowed with exquisite systems of tissue specific transcriptional regulation (Braghetta et al, 1996). This condition adds to the complexity of inhibiting the expression of the Col6a1 gene in vivo by RNAi.…”
Section: Variation Of Interference In Different Tissuesmentioning
confidence: 99%
“…Information on the regulation of expression of collagen VI comes from studies on the ␣1(VI) chain (Braghetta et al, 1996Fabbro et al, 1999;Girotto et al, 2000;Vitale et al, 2001). Regulation is mainly achieved through different enhancers, each of which controls transcription only in a limited set tissues.…”
Section: Introductionmentioning
confidence: 99%